The anti-Marcos struggle personalistic rule and democratic transition in the Philippines - Thompson, Mark R. (Yale University Press, 1995)
In this book Mark Thompson analyzes how Marcos' opponents in the political and economic elite coped with this situation and why their struggle resulted in a transition to democracy through "people power" rather than through violence and revolution.